Why does opera love the Bible? - Afeyan, Natalia (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
When did Bible enter the realm of Opera? Which stories and characters are welcome on an operatic stage and how do they change? What determines the affinity of composers and librettists? Is there a specific biblical dramatism cherished by the operatic authors? How does a musical interpretation revamp biblical characters and plots on the stage? The report is an attempt to answer some of these questions.